La competencia de la Justicia Indígena en el juzgamiento de delitos sexuales. - Roldán Salambay, Silvia Patricia (2023)
In this legal research work, the study of the problem is based, which implies the existence or not of legal competence of the indigenous justice, in the cases in which the prosecution of sexual crimes is presented; in such a way that a conflict between this type of justice and ordinary justice can pre-exist because it is or is not competent to judge this class of crimes, in addition to the effects that this sanction entails. In this way, a study of the administration of indigenous justice has been initiated, which has involved the principle of interculturality, in addition to legal pluralism and indigenous law as such; to later delve into the analysis of sexual crimes, its doctrinal definition, as well as a study from the point of view of the Comprehensive Organic Criminal Code; to focus on the elements that make up this type of crime and analyze more deeply the crime of rape. Finally, the study has focused on the conflict that can arise within the competition between indigenous justice and ordinary justice for the prosecution of sexual crimes, in addition to the effects and consequences of the prosecution of this type of crime within the administration. of indigenous justice.